A CROSS-SECTIONAL STUDY ON KNOWLEDGE, ATTITUDE, AND PRACTICES TOWARDS PREMARITAL SCREENING FOR SICKLE CELL DISEASE AMONG ADULTS IN GOMBE HOSPITAL, BUTAMBALA DISTRICT. - WASIGE, NGONO MOSES; TULYASINGURA, MATHIAS; ojale, moses (Student's Journal of Health Research Africa, 2025)
Background. According to the WHO, 300,000 children with SCD are born worldwide every year. Moreover, about 5% of the world's population carries hemoglobinopathy genes that cause SCD. This study assessed the knowledge, attitudes, and practices of adults towards premarital screening for sickle cell disease at Gombe Hospital, Butambala District. Methodology. The research adopted a descriptive cross-sectional study design using quantitative collection methods. A simple random sampling technique was employed to obtain a desired sample size of 100 respondents. Data was manually tallied using tally sheets, and results were obtained using Microsoft Word and Excel and presented in the form of pie charts and tables. Study results. Most 45 (45%) of the respondents were aged 18-29 years,69(69%) were female, and 939% had attained secondary education. Concerning knowledge, 80(80%) of the respondents were unaware of premarital screening, and 85(85%) were unaware of their hemoglobin genotype. Regarding participants' attitudes,76(76%) believed screening was Important and 63(63%) supported making it mandatory. Practices were limited, with 79(79%) never screened for SCD, although 62(62%) expressed willingness to consider screening in the future. Conclusion. The study revealed low levels of knowledge and limited practices regarding premarital screening for sickle cell disease among adults at Gombe Hospital, despite positive attitudes toward its importance and necessity. There is a need for enhanced education and community awareness to improve understanding and participation in premarital screening initiatives. Recommendation. There is a need for combined efforts from different stakeholders like the government, the Ministry of Health, and health practitioners to ensure couples ready for marriage actively seek information and guidance on premarital screening for sickle cell disease and consider participating in screening together, recognizing it as an essential step in safeguarding their future family health.